Determinants of Vegetable Consumption in Urban Households in Lampung Province - Sayekti , Wuryaningsih Dwi; Lestari, Dyah Aring Hepiana; Prasmatiwi, Fembriarti Erry; Adawiyah, Rabiatul (Jurnal AGRISEP, 2025)
Vegetables have various benefits for the human body, but most people's consumption is still lacking. The purposes of this research were to analyze (1) the vegetable consumption adequacy level and (2) the determinants of the adequacy level of vegetable consumption of urban households in Lampung Province. This study used a descriptive method with secondary data from the 2019 National Socio-Economic Survey (Susenas), from the Central Statistics Agency (BPS) of Lampung Province. A total of 1,500 households were used as samples. The data analysis method used was descriptive and a statistical verification analysis. The results showed that urban households consume an average of 559.37 grams/day, or 152.53 grams/capita/day, of vegetables. The level of household vegetable consumption was still low, with an average of 61.01 percent of the World Health Organization (WHO) recommendation. Household income, number of household members, age of the head of household, the education level of the household's head, and the education level of the housewife positively influenced the adequacy level of household vegetable consumption. The number of household members was the variable that had the greatest influence on the household vegetable consumption level. Income and family size are determinants of adequate vegetable consumption. Therefore, to increase vegetable consumption, the government should educate the community with a focus on allocating income for healthier food. Educational activities can be integrated with ongoing government programs.